Identifying a Disc-shaped Foreign Body - Michael Lee Jr.; Michael George; Kate E. Dorney (Clinical Practice and Cases in Emergency Medicine, 2019)
A four-year-old girl presented to the emergency department vomiting after a foreign body ingestion. An anteroposterior plain radiograph demonstrated a disc-shaped foreign body. Ordinarily, a plain radiograph cannot conclusively identify an object as a coin rather than a button battery that requires emergent removal. However, this high-voltage radiograph, windowed to increase contrast, showed the visible face of George Washington to confirm the diagnosis of an ingested quarter.